A Chinese Chan-Based Mind-Body Intervention Improves Sleep on Patients with Depression: A Randomized Controlled Trial - Agnes S. Chan; Queenie Y. Wong; Sophia L. Sze; Patrick P. K. Kwong; Yvonne M. Y. Han; Mei-chun Cheung (The Scientific World Journal)
Sleep disturbance is a common problem associated with depression, and cognitive-behavioral therapy (CBT) is a more common behavioral intervention for sleep problems. The present study compares the effect of a newly developed Chinese Chan-based intervention, namely Dejian mind-body intervention (DMBI), with the CBT on improving sleep problems of patients with depression. Seventy-five participants diagnosed with major depressive disorder were randomly assigned to receive 10 weekly sessions of CBT or DMBI, or placed on a waitlist. Measurements included ratings by psychiatrists who were blinded to the experimental design, and a standardized questionnaire on sleep quantity and quality was obtained before and after the 10-week intervention. Results indicated that both the CBT and DMBI groups demonstrated significantly reduced sleep onset latency and wake time after sleep onset (effect size range = 0.46–1.0, P≤0.05) as compared to nonsignificant changes in the waitlist group (P>0.1). Furthermore, the DMBI group, but not the CBT or waitlist groups, demonstrated significantly reduced psychiatrist ratings on overall sleep problems (effect size = 1.0, P=0.00) and improved total sleep time (effect size = 0.8, P=0.05) after treatment. The present findings suggest that a Chinese Chan-based mind-body intervention has positive effects on improving sleep in individuals with depression.